Protection of Human Rights of the Accused in the Process of Criminal Investigation - Tran, Thi Thu Hien (H. : ĐHQGHN, 2019)
The investigation in criminal procedure is deemed an important stage with respect to human rights guarantee. During this period, the accused, who is in the most unfavorable position, should be paid attention to and protected. Therefore, this article aims to clarify the scientific legal aspects of human rights of the accused in criminal investigation, indicate some shortcomings in the provisions of Criminal Procedure Code 2015 to offer legal solutions to strengthen the human rights guarantee for the accused in criminal investigation